Distribution volume ratio of serotonin and dopamine transporters in euthymic patients with a history of major depression — a dual-isotope SPECT study - Hsieh, Pei Chun; Lee, I Hui; Yeh, Tzung Lieh; Chen, Kao Chin; Huang, Hui Chun; Chen, Po See; Yang, Yen Kuang; Yao, Wei Jen; Lu, Ru-Band; Chiu, Nan Tsing (Psychiatry research. Neuroimaging, 2010)
Serotonin transporter (SERT) and dopamine transporter (DAT) levels differ in patients with major depression who are in a depressed state in comparison with healthy controls. The aim of this study was to examine the distribution volume ratios (DVRs) of SERT and DAT in drug-free and euthymic patients with a history of major depression. Subjects comprised 13 patients with a history of major depression and 26 sex- and age-matched healthy controls. The euthymic state of depression was defined as a score of 7 or less on the Hamilton Depression Rating Scale. The DVRs of SERT and DAT were approximated using SPECT, with [ 123I] 2-((2-((dimethylamino)methyl)phenyl)thio)-5-iodophenylamine (ADAM) and [ 99mTc] TRODAT-1 as the ligands, respectively. There were no significant differences in the DVRs of SERT or DAT between healthy subjects and euthymic patients with a history of major depression; hence, the SERT and DAT DVRs may not therefore be trait markers for patients with major depression, which helps us to understand more about the pathophysiology of depression.